Minimisasi Kadar Khrom Pada Air Limbah Pelapisan Logam - Siti Agustina; Rahyani Ermawati (Jurnal Kimia dan Kemasan, 1999)
Wastewater from electroplating industries mainly came from plating bath regeneration and rinsing water. The other usually came from pretreatment process, such as washing solution that used for removal oil, rust and other material. The characteristics of electroplating wastewater were very high metal contain in wastewater, especially chrome hexavalent contains. Another type of wastewater with a high and low pH also emitted from electroplating industries. This research was . conducted to investigate the appropriate conditions to minimize chrome contains in wastewater. This research was started by finding out the Oxidize reduction Potential (ORP) and addition of coagulant. And followed by sedimentation process by using 10 % Al2 (C04)3 as a coagulant and an adition of 0,1 % polymer with pH is 10. The result is evaluated by measuring chrome contains in the effluent. The optimal condition of the treatment 15 as follow : Oxidize Reduction Potential (ORP) is 300 mv retention time is 5 menit, and pH is 2.5. And followed by sedimentation process by using 10% Al2(SO 4)3 as a coagulant and an addition of 0, 1 % polymer with pH